2013
DOI: 10.1038/clpt.2013.193
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of CYP2D6 Genotype and Response to Metoprolol CR/XL During Dose Titration in Patients With Heart Failure: A MERIT-HF Substudy

Abstract: To explore the pharmacogenetic effects of the cytochrome P450 (CYP)2D6 genotype in patients with systolic heart failure treated using controlled/extended-release (CR/XL) metoprolol, this study assessed the CYP2D6 locus for the nonfunctional *4 allele (1846G>A; rs3892097) in the Metoprolol CR/XL Randomised Intervention Trial in Congestive Heart Failure (MERIT-HF; n = 605). Participants were characterized as extensive, intermediate, or poor metabolizers (EMs, IMs, or PMs, respectively), based on the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 44 publications
2
57
2
Order By: Relevance
“…In the largest study to date of CYP2D6 genetic polymorphisms and beta-blocker effects (n = 1,533 total with n = 513 metoprolol treated), Bijl et al reported that CYP2D6 PM were treated with significantly lower doses of metoprolol (39) and that CYP2D6 *4 was significantly associated with heart rate, bradycardia, and diastolic blood pressure in patients treated with metoprolol (39). In contrast to our findings and those reported by Rau et al and Bijl et al , Batty et al did not find a significant association between CYP2D6 *4 and metoprolol dose in their pharmacogenetic sub-study of the MERIT-HF trial (11). As the only study reported on the association of CYP2D6 *4 and clinical outcomes, the study reported by Batty et al did not find significant differences among CYP2D6* 4 genotypes in all-cause mortality or rate of hospitalization (11).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the largest study to date of CYP2D6 genetic polymorphisms and beta-blocker effects (n = 1,533 total with n = 513 metoprolol treated), Bijl et al reported that CYP2D6 PM were treated with significantly lower doses of metoprolol (39) and that CYP2D6 *4 was significantly associated with heart rate, bradycardia, and diastolic blood pressure in patients treated with metoprolol (39). In contrast to our findings and those reported by Rau et al and Bijl et al , Batty et al did not find a significant association between CYP2D6 *4 and metoprolol dose in their pharmacogenetic sub-study of the MERIT-HF trial (11). As the only study reported on the association of CYP2D6 *4 and clinical outcomes, the study reported by Batty et al did not find significant differences among CYP2D6* 4 genotypes in all-cause mortality or rate of hospitalization (11).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings and those reported by Rau et al and Bijl et al , Batty et al did not find a significant association between CYP2D6 *4 and metoprolol dose in their pharmacogenetic sub-study of the MERIT-HF trial (11). As the only study reported on the association of CYP2D6 *4 and clinical outcomes, the study reported by Batty et al did not find significant differences among CYP2D6* 4 genotypes in all-cause mortality or rate of hospitalization (11). The lack of association between CYP2D6 *4 and clinical outcomes reported by Batty et al may have been secondary to an inherent decrease in statistical power (decreased sample size and increased number of comparison groups) characteristic of retrospective genetic sub-study analyses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…After correcting for the multiple testing, none of them qualified as significant. Furthermore, among the 19 imputed SNPs, the non-functional variant of the CYP2D6 gene ( CYP2D6*4; rs3892097) identified by other investigators 44, 45 was also tested, but it did not show a significant association with risk for postoperative AF, despite perioperative BB prophylaxis (MAF = 0.15; OR = 0.86; 95% CI: 0.56-1.34; P = 0.51). Several reasons may account for this negative replication for CYP2D6 including variation in study design, the use of imputed data, dose and/or type of BBs used.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher drug plasma concentrations of metoprolol and carvedilol have been reported among CYP2D6 poor metabolizers compared to those with other phenotypes. 5558 While the poor metabolizer phenotype has also been associated with greater heart rate and diastolic blood pressure response to β-blockers, results are inconsistent. 5661 Inconsistent associations between genotype with clinical response to metoprolol is likely a reflection of the wide therapeutic index of β-blockers where differences in plasma concentrations may or may not result in clinically significant effects.…”
Section: β-Blocker Pharmacogenomicsmentioning
confidence: 99%